Solar chargers based on new dye-based photovoltaic modules and new supercapacitors - Plebankiewicz, Ireneusz; Bogdanowicz, Krzysztof. A.; Kwaśnicki, Paweł; Skunik-Nuckowska, Magdalena; Rączka, Patryk M.; Kulesza, Paweł; Iwan, Agnieszka; Przybył, Wojciech (Bulletin of the Polish Academy of Sciences Technical Sciences, 2023)
Electricity storage is one of the best-known methods of balancing the energy supply and demand at a given moment. The article presents an innovative solution for the construction of an electric energy storage device obtained from an innovative photovoltaic panel made of new dye-based photovoltaic modules and newly developed supercapacitors – which can be used as an emergency power source. In the paper, for the first time, we focused on the successful paring of new dye-sensitized solar cell (DSSC) with novel supercapacitors. In the first step, a microprocessor stand was constructed using Artificial Intelligence algorithms to control the parameters of the environment, as well as the solar charger composed of six DSSC cells with the dimensions of 100_100 mm and 126 CR2032 coin cells with a total capacitance of 60 F containing redox-active aqueous electrolyte. It was proven that the solar charger store enough energy to power, i.e. SOS transmitter or igniters, using a 5 V signal.